CODING for Middle Schoolers. - PIERCE, MARCO (Education Digest, 2013)
The article discusses the teaching of computer programming languages, adapted from the article "Coding for Middle Schoolers: Next-Generation Programming Languages Are Teaching Young Students How to Code to Learn," by Margo Pierce, in the May 2013 issue of "T.H.E. Journal."